Epidemiological profile of women admitted for migraine and other headache syndromes in the southern region of Brazil, between 2018 and 2023 - Calixto Caetano, Maria Clara; Lopes Brandão, Brenda; Boreggio, Hugo Berdejo; Silva, Júlia Esteca da; Schuch, Karolina Lemos; Stetter, Letícia Loreta Roque; Oliveira , Lorena Pedro de; Mota, Nicolas França; Silva, Celijane Almeida (Headache Medicine, 2024)
Introduction: Migraine is a chronic neurological disorder that negativelyinfluences personal, economic, and social aspects of individuals’ lives, as wellas reducing health-related quality of life. Its highest incidence occurs amongmiddle-aged individuals, with women being the most affected. Regardingmonthly headache days, about one-third of migraine sufferers experience four or more days, and approximately 7% have 15 or more days. Acute therapy aimsto alleviate pain and restore function during attacks, while preventive treatmentaims to reduce the frequency and severity of episodes. Disease progressioncan occur in some individuals, underscoring the importance for physicians toidentify modifiable risk factors to enhance patients’ quality of life. The majority ofmigraine sufferers seek medical care in primary healthcare settings, highlightingthe critical need for these professionals to be prepared to manage the condition. Objective: To identify the epidemiological profile of women hospitalized for migraine and other headache syndromes in the Southern region of Brazilbetween 2018 and 2023. Methods: Ecological, cross-sectional, retrospective, and descriptive studyconducted through data collection from the Hospital Information System of theUnified Health System (SIH/SUS), linked to DATASUS, focusing on variablessuch as age, race/ethnicity, type of care, and hospital service costs. Results: A total of 16,488 women were hospitalized for migraine and otherheadache syndromes. The year 2019 had the highest number of admissions(4,052), while 2021 had the lowest (1,820). Of these, 17.3% (2,907) werewomen aged 40-49 years, 16.8% were aged 30-39 years, 15.4% were aged 20-29 years, and the least affected age group was under 1 year (0.1% - 18 cases). Regarding race/ethnicity, 81.6% (13,449) were White, 8.8% (1,450) were MixedRace, 2.5% (418) were Black, 0.7% (117) were Yellow, 0.02% (4) wereIndigenous, and 6.3% (1,050) did not have race information available. 93.5% ofadmissions were for urgent care, while only 6.5% were elective. The total hospital service costs during this period amounted to R 7,755,801.34, with2019 having the highest cost (R 2,100,630.40) and 2021 the lowest (R 762,862.42). The age group with the highest costs was 40-49 years (R 1,467,777.68), while the lowest was under 1 year (R 2,820.53). Conclusion: This study reveals, through the epidemiological profile of womenhospitalized for migraine and other headache syndromes in the Southern regionof Brazil between 2018 and 2023, that 2019 had the highest number ofadmissions and highest costs. The most affected age group, and consequentlythe most costly, was 40-49 years old. White individuals were the most affectedby race, and the majority of admissions were for urgent care. Therefore, understanding the specific epidemiological patterns of this condition in thesepatients is crucial for providing adequate and personalized healthcare.